Edukasi Stretching Efektif Saat Aktivitas Olahraga Pada Siswa Ekstrakurikuler Basket SMPN 05 Malang - Dinda Permata Putri; Qonita Nabila; Umbu Simon Panyonga; Syarif Hidayatullah; Ika Niswatul Chamidah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Physical activity is a form of physical movement that results from the body's systems, one of which is the musculoskeletal system. Physical activity requires energy expenditure in the process. One of physical activity that is often done is exercise. High levels of activity can cause muscle fatigue, tissue damage, pain and discomfort. Proper and effective exercise preparation can have an effect on improving body health such as blood circulation, metabolism, and increasing muscle strength and work. One of important exercise preparation is stretching. Stretching exercises that are carried out well and regularly have benefits in maintaining and improving quality and increasing the flexibility of the body.